Anticoagulation for Left Ventricular Thrombosis Post-Myocardial Infarction - Current Recommendations and Future Perspectives - Haba Mihai Ștefan Cristian; Ungurenașu Andreea-Simona; Ciobanu Elena Cosmina; Mitu Florin; Miftode Radu Stefan; Mitu Ovidiu (Sciendo, 2022)
Left ventricular thrombosis (LVT) is one of the most severe complications of acute myocardial infarction (AMI). LVT is commonly associated with an increased risk of cerebral or systemic embolization, which furthermore increases the morbidity and mortality of these patients. Management of LVT implies the administration of anticoagulants to achieve thrombus resolution and reduce the embolic risk. However, in the setting of an AMI, anticoagulants are added to already existing antiplatelet therapy, which increases the bleeding risk for this category of patients. Vitamin K antagonist (VKA) represents the main guideline recommendation for anticoagulation, but its multiple interactions are associated with an increased number of patients who are outside the therapeutic range and low compliance. Early studies that evaluate direct oral anticoagulants (DOAC) as an alternative for VKA show promising results, with reduced strokes and bleeding rates and faster thrombus resolution. Thus, in the near future, DOAC may represent a therapeutic option for treating LVT, but larger studies are needed to validate this approach.